KAJIAN FILOSOFIS TENTANG KONSEP KEADILAN DARI PEMIKIRAN KLASIK SAMPAI PEMIKIRAN MODERN - Johan Nasution, Bahder (Yustisia, 2014)
AbstractJustice, since the first issue, has been the subject of study both among philosophers and among theologians, politicians and thinkers or legal experts. However, if there are questions about justice, could not be determined what measures are used to determine something is fair or not. Various answers about justice usually never or rarely satisfying so that continues to be debated, so it can be concluded that the various formulations of justice is a relative statement. This issue ultimately encourages many people to take a shortcut by submitting formulation of justice to the legislators and judges who will formulate it based on their own considerations.Keywords : Philosophy, justiceAbstrakMasalah keadilan sejak dahulu telah menjadi bahan kajian baik dikalangan ahli filsafat maupun dikalangan agamawan, politikus maupun para pemikir atau ahli hukum. Pertanyaan tetang keadilan, tidak bisa ditentukan ukuran yang digunakan untuk menentukan sesuatu itu adil atau tidak. Berbagai jawaban tentang keadilan biasanya tidak pernah atau jarang yang memuaskan sehingga terus menjadi perdebatan, dengan demikian rumusan mengenai keadilan merupakan rumusan yang relatif. Persoalan ini pada akhirnya mendorong banyak kalangan untuk mengambil jalan pintas dengan menyerahkan perumusan keadilan kepada pembentuk undang-undang dan hakim yang akan merumuskannya berdasarkan pertimbangan mereka sendiri.Keywords: Kajian Filosofis, Konsep Keadilan